Parallel Algorithms for Distinguishing Nondeterministic Finite State Machines - Ali, Mustafa (2015)
A Master of Science thesis in Computer Engineering by Mustafa Ali entitled, "Parallel Algorithms for Distinguishing Nondeterministic Finite State Machines," submitted in February 2015. Thesis advisor is Dr. Gerassimos Barlas and thesis co-advisor is Dr. Khaled El-Fakih. Soft and hard copy available.